الكاريكاتير بين الحق في الإعلام والحق في الصورة -تداعيات أزمة الرسوم بين لولاند بوسطن الدنماركية وشارلي إيبدو الفرنسية- - جلول خلاف (مجلة الآداب و العلوم الإجتماعية, 2015)
In this paper, we tried to present an image of the repercussions of the Cartoons Crisis caused by the Western Press after publishing the Danish Cartoons; from the point of view of the Freedom of Opinion and Speech drawled by the West aiming at offending the Arab and Muslim People; through the relation between the journalist right to information, the person's right to privacy and the peoples’ right to their symbols; explaining how its laws and legislations contradict this thesis by quoting some of these laws. We also showed, in this paper, the importance of the Caricature as journalistic art benefiting of considerable freedom that exceeds the rest of the journalistic arts, changing it from the humoristic function to that of aggression; then the point of view of the other great Monotheistic Religions on the issue of cartoons and giving offence to the others by mockery and defamation in the Monotheistic Religions and secular laws. Finally, we elucidate the difference between the Public and Private Figures; showing that the first one can be criticised considering it as a public property. At last, a general set of this research findings were exposed.